Theoretical Perspectives in Dynamic Action-Based Professions - Betty Andersen; Margaret McMillan (Halla Newcastle Education and Research Center, 2015)
This paper addresses the issue of the generation of theory from practice and outlines in some detail the process of theory development engaged in by Andersen, an Australian nurse theorist and the designer of an integrated curriculum reliant on the philosophy and methodology of Problem-based Learning. In particular, Dewey's theory in expounding the relationship between thought, judgement and action is shown to be of clear relevance to nursing practice and therefore to any reflection on that practice. Five key questions were identified as significant in directing the enquiry and reflective processes adopted. Reviews of the collegial processes of spanning 45 years allowed identification and confirmation of key characteristics of theory development which is derived from action-taking. The outcome of the development of the initial activity is presented as a series of interactive models and frameworks which presents a systematic view of the phenomenon of nursing. This view of theory development is both explanatory and predictive and allows the structure of the discipline of nursing as both an academic and practice activity to emerge.